Metaphysics of Nothingness: Heidegger, Ibn ‘Arabi and Nagarjuna: Heidegger, Ibn ‘Arabi & Nagarjuna - Naeim, Fauzi (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2019)
For this article, the author attempts to describe the metaphysics of nothingness from three sources; Martin Heidegger, Ibn ‘Arabi and Nagarjuna. Each of the philosophers engages the intimation of ‘the nothing’ to fathom the existential question of being, reality and logic. The idea for the article was influenced by Heidegger's seminal text “What is Metaphysic?” (1929/1998). Heidegger writes how human “a being held out into the nothing.” Why and how is human holding out into the nothingness? What are the boundaries that form this nothingness? Rather than risk into pessimistic existentialism, the author pursues the question of nihilism in the nothingness with the kind of joy, as Heidegger would say it: “Secret alliance with the cheerfulness and gentleness of creative longing.” With three different thinkers from different eras – Heidegger was a German philosopher but brought up with Christian teachings, Ibn ‘Arabi was an Andalusian Islamic Sufi whereas Nagarjuna was an Indian-Buddhist teacher – it is hoped that the idea about nothingness can be grappled and if not, be meditated upon. Keywords: Martin Heidegger, Ibn ‘Arabi, Nagarjuna, nothingness, metaphysics